2015
DOI: 10.1002/aic.14897
|View full text |Cite
|
Sign up to set email alerts
|

Shear dispersion in combined pressure‐driven and electro‐osmotic flows in a capillary tube with a porous wall

Abstract: An analytical expression is derived for the shear dispersion during transport of a neutral nonreacting solute within a coupled system comprised of a capillary tube and a porous medium under the combined effects of pressure‐driven and electro‐osmotic flows. We use the Reynolds decomposition technique to obtain a dispersion coefficient by considering a sufficiently low wall or zeta potential that accounts for the combined flows. The coupled dispersion coefficient depends on the Debye–Hückel parameter, Poiseuille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Considering water slip phenomenon, the boundary condition of water transport through elliptical nanopores can be described by the following equation. [55][56][57] v…”
Section: Water Viscosity In the Elliptical Nanoporesmentioning
confidence: 99%
“…Considering water slip phenomenon, the boundary condition of water transport through elliptical nanopores can be described by the following equation. [55][56][57] v…”
Section: Water Viscosity In the Elliptical Nanoporesmentioning
confidence: 99%
“…[9][10][11][12][13]20,24] A detailed review of these assumptions can be found elsewhere. [12,13] By taking into consideration these assumptions and using Equation (2) and making some rearrangements, Equation (7) reduces to the following:…”
Section: Governing Equationmentioning
confidence: 99%
“…Now, we apply three significant assumptions adopted from Taylor [14] and Fischer et al [20] for determination of a dispersion coefficient during dispersive chemical species transport. These assumptions are as follows: the chemical species transport occurs under a quasisteady state condition (@C 0 D =@t D % 0), [9][10][11][12][13][14][20][21][22][23] C 0 D is a slowly varying function, [20] and the longitudinal advection is dominant compared to the longitudinal diffusion (…”
Section: Governing Equationmentioning
confidence: 99%
See 2 more Smart Citations